IN VITRO SCREENING AND CORRELATION OF ETHANOLIC PEEL EXTRACTS OF PUNICA GRANATUM AND CITRUS SINENSIS WITH RESPECT TO ANTIOXIDANT AND ANTIRADICAL ACTIVITY - V SONTAKKE, AJIT; S HENDRE, ANUP; R PATIL, SANGITA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study is to evaluate the effect of the ethanolic peel extracts of Punica granatum and Citrus sinensis on total phenolics, total antioxidants, and radical scavenging activities using different in vitro models. Methods: Pomegranate and orange fruits at the maturity stage were manually peeled, washed, and air dried before extraction. Dried peels were grinded, weighed, and extracted with 95% ethanol and were used for in vitro analysis. Different concentrations of extracts for each peel were prepared. Total phenolics content, total antioxidant capacity, and free radical scavenging activities of each peel extract were estimated in the form of Folin–Ciocalteu reagent assay, phosphomolybdenum assay, hydroxyl free radical scavenging assay, and superoxide free radical scavenging assay, respectively. Results: The ethanolic peel extracts of P. granatum and C. sinensis showed significant increased total phenolic contents and total antioxidant activity. Furthermore, radical scavenging activity (hydroxyl and superoxide) was found to be significant in both ethanolic peel extracts. Conclusion: It can be concluded from the study that the ethanolic peel extracts of P. granatum and C. sinensis has potential antioxidant and antiradical activity.